Contraceptive Potential of Methanol Leaf Extract of Ananas comosus In Female Wistar Rats - Johnson EI; Ekanem AU; Bassey E; Nwafor P (Ibom Medical Journal)
Background: Traditionally, Ananas comosus leaf is used locally to prevent pregnancy among the indians.